BRAND IMAGE, PRICE, AND FACILITIES AFFECT CONSUMER DECISIONS USING TOURISM BUS SERVICES (SURVEY ON CONSUMERS PT. KUSUMA TRANS IN KLATEN REGENCY) - Kusuma Minarta, Muhamad; Wijiastuti, Sri; Darsono , Darsono (International Journal of Business, Law, and Education, 2023)
PT Kusuma Trans is a company engaged in consumer tourism transportation services. To maintain customer satisfaction at Pt Kusuma Trans always strives to meet the needs of consumers, one of which is to increase introduction to the public about the products of services provided to get a good image, pricing following market capabilities and provide comfortable facilities for bus users. This study aims to determine the influence of brand image, price, and facilities on consumer decisions to use the services of the Tourism bus P.T. Kusuma Trans in Klaten regency, Central Java. This research method uses survey research—data collection using questionnaires with the Likert scale and data analysis using multiple linear regression. The results of this study showed that the value of the constant (a): 3.552 marked positive, variable coefficient brand image 0.273, variable coefficient price 0.229, variable coefficient facilities 0.215. This study concludes that Brand image, price, and facilities significantly affect consumer decisions to use the services of the Tourism bus P.T. Kusuma Trans in Klaten.